Pre-clinical evaluation of soybean-based wound dressings and dermal substitute formulations in pig healing and non-healing in vivo models - Rostislav V Shevchenko; Matteo Santin (Burns & Trauma, 2014)
In the last decade, a new class of natural biomaterials derived from de-fatted soybean flour processed by either thermoset or extraction procedures has been developed. These biomaterials uniquely combine adaptability to various clinical applications to proven tissue regeneration properties. In the present work, the biomaterials were formulated either as hydrogel or as paste formulation and their potential as wound dressing material or as dermal substitute was assessed by two in vivo models in pig skin: The healing full-thickness punch biopsy model and the non-healing full-thickness polytetrafluoroethylene (PTFE) chamber model. The results clearly show that collagen deposition is induced by the presence of these biomaterials. A unique pattern of early inflammatory response, eliciting neutrophils and controlling macrophage infiltration, is followed by tissue cell colonization of the wound bed with a significant deposition of collagen fibers. The study also highlighted the importance in the use of optimal formulations and appropriate handling upon implantation. In large size, non-healing wounds, wound dermis was best obtained with the paste formulation as hydrogels appeared to be too loose to ensure lasting scaffolding properties. On the contrary, packing of the granules during the application of paste reduced biomaterial degradation rate and prevent the penetration of newly vascularized tissue, thus impeding grafting of split-thickness autologous skin grafts on the dermal substitute base.